Working on optical characterization setup for cutting-edge silicon photonics technology : part 2 - Chui, Javier Chia Thye (2019)
Data and signal transmissions have slowly evolved over the years from traditional method such as electrical signals to optical signals for more efficiency. Electrical methods have to include losses such as heat which makes designing of the cables and parameters bulky especially for long distances transmission. This is where this project aims to reduce all these inefficiencies even for short distance transmission by using optical signals instead of electrical signals. Studying the characteristics and hence, determining the viability of using such methods in short distances transmission.